1994
DOI: 10.1007/bf01875769
|View full text |Cite
|
Sign up to set email alerts
|

A discussion of current attachment research and its clinical applications

Abstract: This article highlights Stern's recent conceptualization of the infant's development of internal working models of attachment and the relationship between internal working models and the narrative self. Research studies, including Ainsworth's and Main's seminal work on types of infant attachment models, are reviewed. These include secure, avoidant insecure, ambivalent insecure, and disorganized-disoriented types of infant attachment. Later research supports the continuation of these same attachment patterns in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Further information about abused and neglected children's internal working models has been produced experimentally by using story-stem techniques, eg Fish and Condon (1994). These models were very persistent, even when children's behaviour had matured (Main et al, 1985).…”
Section: Internal Working Model In 'Overt Losses'mentioning
confidence: 99%
“…Further information about abused and neglected children's internal working models has been produced experimentally by using story-stem techniques, eg Fish and Condon (1994). These models were very persistent, even when children's behaviour had matured (Main et al, 1985).…”
Section: Internal Working Model In 'Overt Losses'mentioning
confidence: 99%
“…Recently, John Byng-Hall (1990) reported that he uses the theory as a way to conceptualize relationships in terms of shared scripts or working models of attachment behavior that have transgenerational implications. Several authors have argued, in fact, that attachment theory does not suggest a new school of psychotherapy or counseling practice, but rather that it provides a theoretical framework for understanding the principles which underlie all effective therapies (Biringen, 1994;Farber et al, 1995;Fish and Condon, 1994;Jones, 1983;Lopez, 1995).…”
mentioning
confidence: 99%